2004
DOI: 10.1002/jcla.20012
|View full text |Cite
|
Sign up to set email alerts
|

Reference distributions for alpha2‐macroglobulin: A practical, simple and clinically relevant approach in a large cohort

Abstract: In this 11th article in a series, reference values of serum levels alpha(2)-macroglobulin alpha(2)M) are examined. The study is based on a cohort of 40,420 Caucasian individuals from northern New England that were tested in our laboratory between 1994 and 2000. Measurements were standardized against Certified Reference Material (CRM 470)/Reference Preparation for Proteins in Human Serum (RPPHS) and the results analyzed using a previously described statistical approach. Individuals with unequivocal laboratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
2
22
0
1
Order By: Relevance
“…The stoichiometry of hrPrP, RNA and a2M had a dramatic effect on the structures of the complexes formed and may have biological significance as plasma levels of a2M vary with age, sex and disease [19]. Co-incubation of hrPrP, RNA and a2M led to the formation of aggregates containing fibril-like structures and consistent with an amyloid-like structure when stained with Congo red.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The stoichiometry of hrPrP, RNA and a2M had a dramatic effect on the structures of the complexes formed and may have biological significance as plasma levels of a2M vary with age, sex and disease [19]. Co-incubation of hrPrP, RNA and a2M led to the formation of aggregates containing fibril-like structures and consistent with an amyloid-like structure when stained with Congo red.…”
Section: Resultsmentioning
confidence: 93%
“…Discussion a2M, a component of blood [19] and CSF [14], and PrP, a cell surface protein of neurons [20], lymphocytes [21] and endothelial cells [22] are able to interact in a biological context. Biological interaction between cationic PrP and anionic a2M is supported by co-immunoprecipitation results from brain homogenate.…”
Section: Resultsmentioning
confidence: 99%
“…Other biochemical parameters like haptoglobin which decreases in cases of intra-vascular haemolysis and increases in inflammatory states, may vary. α2-macroglobulin increases in cases of inflammation or nephrotic syndrome [35]. Taking all these data collectively, the discrimination ability of the SteatoTest in our population is not surprising.…”
Section: Discrimination Ability (Roc Analysis)mentioning
confidence: 82%
“…Fibrinogen levels correlate with total cholesterol and LDL-cholesterol as well as with age [26]. A study investigating a-2-macroglobulin levels in a large group (n = 40,420) reported a steady increase after the age of 45, with females having constantly higher mean a-2-macroglobulin levels [27]. A review of the available literature came to very similar findings, reporting an increase in a-2-macroglobulin levels after the age of 40-50, with constantly higher mean values for females [28].…”
Section: Rationale Of Plasmapheresis For Ishlmentioning
confidence: 96%